Effect of Sport Shoe Weight on Gait Kinetics in Athletes With Anterior Cruciate Ligament Reconstruction During Walking - AmirAli Jafarnezhadgero; Milad Piran Hamlabadi; Masomeh Naderpour; Majid Khodabakhsh Dizaj (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Different shoe weights affect the gait mechanics. Some dynamic changes or adjustments induced by anterior cruciate ligament (ACL) reconstruction can be assessed through the analysis of the ground reaction forces (GRFs). This study aims to determine the effect of sports shoe weight on gait kinetics in athletes with ACL reconstruction.Methods Twenty healthy men and 20 athletes with ACL reconstruction volunteered to participate in this study. Each participant performed three walking trials with shoes having light (weight: 150±18 g), moderate (300±18 g), and heavy (450±18 g) weights in a randomized order. The GRFs were analyzed during shod walking. Results The GRF component at vertical direction during the heel contact phase changed significantly during the use of shoes with different weights (P=0.001). In addition, the GRF at vertical direction during the push-off phase and GRF at mediolateral direction during the push-off phase increased significantly (P=0.023 and 0.014, respectively).Conclusion The biomechanics of lower limbs and the GRFs are significantly different when using light and heavy shoes during the heal contact and push-off phases of walking.